An Analysis of a Demand Charge Electricity Grid Tariff in the Residential Sector - Andreas V. Stokke; Gerard L. Doorman; Torgeir Ericson (Statistics Norway, Research Department, 2009)
This paper analyses the demand response from residential electricity consumers to a demand charge grid tariff. The tariff charges the maximum hourly peak consumption in each of the winter months January, February and December, thus giving incentives to reduce peak consumption. We use hourly electricity consumption data from 443 households, as well as data on their network and power prices, the local temperature, wind speed and hours of daylight. The panel data set is analysed with a fixed effects regression model. The estimates indicate a demand reduction between 0.07 and 0.27 kWh/h in response to the tariff. This is on average a 5 percent reduction, with a maximum reduction of 9 percent in hour 8. The consumers did not receive any information on their continuous consumption or any reminders when the tariff was in effect. It is likely that the consumption reductions would have been even higher with more information to the consumers.
Keywords: D10; Q40; 330; Electricity consumption; demand charge tariff; demand response